BOUNDARY TREATMENT TECHNIQUES IN SMOOTHED PARTICLE HYDRODYNAMICS: IMPLEMENTATIONS IN FLUID AND THERMAL SCIENCES AND RESULTS ANALYSIS - Fraga Filho, Carlos Alberto Dutra; Aquije Chacaltana, Julio Tomás (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Appropriate boundary treatment technique is one of the greatest challenges found in the Smoothed Particle Hydrodynamics (SPH) Lagrangian method. This paper focuses on the treatment of different boundary condition techniques and their implementation in the SPH code developed by the authors. The boundary conditions implemented and tested in this work involve the use of virtual particles, repulsive force, geometric reflection, and dynamic particle treatments. A code was written in Fortran language in order to solve the system of algebraic equations that result from the application of the SPH method in the discretization of the conservation equations. The implemented boundary conditions are tested and the numerical results are compared with results from non-commercial codes and analytical ones. In general, the numerical results obtained in the present work are in agreement with those reported in the literature.